152k views
2 votes
Help me please!!!!!!!!!

Help me please!!!!!!!!!-example-1
User IAmDranged
by
5.9k points

1 Answer

3 votes

Answer:

(x + 1)(5x - 3)

Explanation:

Given

5x² + 2x - 3

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term, that is

product = 5 × - 3 = - 15 and sum = + 2

The factors are + 5 and - 3

Use these factors to split the x- term

5x² + 5x - 3x - 3 ( factor the first/second and third/fourth terms )

= 5x(x + 1) - 3(x + 1) ← factor out (x + 1) from each term

= (x + 1)(5x - 3) ← in factored form

User SSS
by
6.3k points